2020
DOI: 10.1140/epjd/e2019-100436-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of observables in a q-deformed harmonic oscillator

Abstract: Chaos in classical systems has been studied in plenty over many years. Although the search for chaos in quantum systems has been an area of prominent research over the last few decades, the detailed analysis of many inherently chaotic quantum systems based on expectation values of dynamical variables has not been reported in the literature. In this paper, we extend the study of dynamical behaviour using expectation values of variables to a q-deformed harmonic oscillator. The system is found to be periodic, qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…It has been demonstrated that the time series of the anticipated values of dynamic variables, such as observables related to position and momentum, display periodic, quasi-periodic, or chaotic behavior contingent upon the deformation parameter q [13]. Similarly, in this scenario, we have distinctly observed the indications of periodic, quasi-periodic, or chaotic behavior in the entanglement dynamics of the system.…”
Section: Field Initially In the Deformed Coherent Statesupporting
confidence: 56%
See 1 more Smart Citation
“…It has been demonstrated that the time series of the anticipated values of dynamic variables, such as observables related to position and momentum, display periodic, quasi-periodic, or chaotic behavior contingent upon the deformation parameter q [13]. Similarly, in this scenario, we have distinctly observed the indications of periodic, quasi-periodic, or chaotic behavior in the entanglement dynamics of the system.…”
Section: Field Initially In the Deformed Coherent Statesupporting
confidence: 56%
“…A comprehensive discourse on the qdeformed generalized Weyl algebra can be found in [12]. A recent study on the dynamics of the math-type qdeformed harmonic oscillator revealed the signatures of chaos in the system [13]. The realization of the thermostatistics of q-deformed algebra can be built on the formalism of q-calculus [14].…”
Section: Introductionmentioning
confidence: 99%
“…We will focus on q deformations of SU(2)-like algebras. For a better understanding of q deformations and their various applications, we direct the readers' attention to the references [85][86][87][88][89][90][91][92][93][94][95].…”
Section: Q-deformed Su(2) Algebra and Lanczos Coefficientsmentioning
confidence: 99%
“…Various dynamic equations of NLSE type with q-deformed potentials have been proposed to model q-deformed processes in nuclear and atomic physics (see i.e. [55][56][57] and the references therein), and very recently Nutku et al studied the complexity of q-deformed quantum harmonic oscillator [58].…”
Section: Introductionmentioning
confidence: 99%